Nutrient Limiting Factor for Enabling Algae Growth of Rawapening Lake, Indonesia - Agatha Sih Piranti; Diana Retna Utarini Suci Rahayu; Gentur Waluyo (Biosaintifika: Journal of Biology & Biology Education, 2018)
Two important issues for establishment of nutrient criteria are identifying which nutrient limits algal growth and determining the concentration of that nutrient enabling nuisance growths. The purposes of this research were: 1) to examine the nutrient (TN, TP, ratio of TN/TP) dynamic in Rawapening Lake spatially and temporally, 2) to identify Nutrient Limiting of Algal Growth in Rawapening Lake, and 2) to determine the nutrient criteria for enabling algae growth in Rawapening Lake. The research was conducted using a survey method in 7 sites from February to August 2016. The result showed that spatially Total Nitrogen (TN) and Total Phosphor (TP) in the lake were not evenly distributed and temporally influenced by the inflow. The development of algae biomass in Rawapening Lake determined ratio of TN/TP. Nutrient criteria as follow: oligotrophic was 5.96 - 14.39, mesotrophic was 14.39 - 42.15, eutrophic 42.15 - 51.65, and hyper-eutrophic 51.65. These criteria could be used in designing controlling eutrophication problem by arranging nutrient input from both external and internal sources in order to meet those limit. The benefits of research contributes to the development of environmental monitoring methods to assess the trophic status using more appropriate in accordance with the conditions of the tropics region. It also could be used for consideration in policy direction and orientation of land use in catchment areas in relation to water quality of the lake.